Transformations of 1-(Oxiranylmethyl)-1,2,3-triazoles into 2-(Oxiranylmethyl)-1,2,3-triazoles and Alkanenitriles - Osawa, Ayumi; Mera, Akane; Namba, Kosuke; Tanino, Keiji (Synlett, 2013)
New reactions for the transformation of 1-(oxiranylmethyl)-1,2,3-triazoles into 2-(oxiranylmethyl)-1,2,3-triazoles or alkanenitriles were established. Successive treatment of the substrate with triflic acid and t-BuOH afforded 4,6-dihydro-5-hydroxy-1,3a,6a-triazapentalene derivative. Under the influence of NaH, the bicyclic compound was converted into a 2-(oxiranylmethyl)-1,2,3-triazole or an alkanenitrile. The reaction pathway depends on the substituent pattern of the epoxide side chain.
Keywords: 1,2,3-triazole; 2-substituted 1,2,3-triazole; click reaction